STRATEGI PENANGKALAN SURIAH DALAM MENGHADAPI SERANGAN UDARA ISRAEL PERIODE 2015-2019 - Restu Maulidiya, (2020)
The contestation that occurred in the Middle East region has always been an interesting thing to discuss. Not only did it bring about major changes to the political scenario and strategy adopted by the countries in the region, but it also disrupted the national security of each country. Syria one of them, put a deterrence strategy in an effort to deal with Israel's pre-emtive strike by air, as a result of the contestation that occurred in the Middle East region. This is a form of Syria's responsibility in protecting its country and returning the country's status quo again. Using a qualitative research methodology and the concept of a deterrence strategy and national security, this paper attempts to explain how the deterrence strategy carried out by Syria can protect its national security from preliminary attacks launched by Israel. As a result, this deterrence strategy is able to minimize Israeli attacks in some Syrian areas. Interestingly, in an effort to carry out this strategy Syria is assisted by Iran, Hezbollah (Lebanon) and Russia. Assistance from the three countries, effectively giving changes to Israel to think again to attack Syria.